Nursing management for a patient with erysipelas infection leads to sepsis combined with multiple organ dysfunction syndromes (1例丹毒感染致脓毒症合并多功能脏器衰竭患者的护理体会) - ZHOU Jie (周洁); REN Yaxing (任亚星); TANG Ling (唐玲); LI Ye (李野); ZHANG Jing (张敬); ZHANG Tingting (张婷婷); LIU Huan (刘欢); LI Shuo (李硕); GAO Chunli (高春利); DONG Ying (董樱) (Association of Integrative Nursing, 2021)
This paper reviewed nursing management for a patient with erysipelas infection leads to sepsis combined with multiple organ dysfunction syndromes. A comprehensive treatment including anti-infective therapy, diuretic treatment, cardiac medication and circulation function treatment and related nursing management was carried out. Targeted nursing strategies including non-invasive ventilation nursing, medication care and fluid-management, fever nursing, catheter maintenance, skin care were carried out to ensure the therapeutic efficacy and symptom relieving. (本文总结1例丹毒感染致脓毒症合并多功能脏器衰竭患者的护理措施, 在给予抗感染、利尿、强心、维持循环功能治疗的同时还要加强护理, 从无创通气护理、用药监护及液体管理、发热护理、管路护理、皮肤护理等方面给予以针对性护理干预, 确保有效改善患者症状。)